1976
DOI: 10.1017/s0022143000013708
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of a Three-Dimensional Non-Isothermal Glacier

Abstract: A mathematical model is constructed for land glaciers with the thickness much less than the horizontal dimensions and radii of curvature of large bottom irregularities by means of the method of a thin boundary layer in dimensionless orthogonal coordinates. The dynamics are described by a statically determinate system of equations, so the solution for stresses is found. For the general non-isothermal case the interrelated velocity and temperature distributions are calculated by means of the iteration of solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Using an idea that Oerlemans [1982] had applied earlier to the much longer 100,000-year glacial cycle, MacAyeal [1993] emphasized the importance of the upward geothermal flux at the base of massive ice sheets in accounting for the necessary basal melting conditions. On the other hand, Verbitsky and Saltzman (henceforth called V-S) [1993,1994], following ideas presented earlier by Grigoryan et al [1976], suggested In the following section we present the general formula for basal temperature derived by V-S [1994] from the basic glaciological thermohydrodynamical equations. This formula is used to define two nondimensional numbers by which we can compare the magnitude of the different contributions to the basal temperature for the present and past ice sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Using an idea that Oerlemans [1982] had applied earlier to the much longer 100,000-year glacial cycle, MacAyeal [1993] emphasized the importance of the upward geothermal flux at the base of massive ice sheets in accounting for the necessary basal melting conditions. On the other hand, Verbitsky and Saltzman (henceforth called V-S) [1993,1994], following ideas presented earlier by Grigoryan et al [1976], suggested In the following section we present the general formula for basal temperature derived by V-S [1994] from the basic glaciological thermohydrodynamical equations. This formula is used to define two nondimensional numbers by which we can compare the magnitude of the different contributions to the basal temperature for the present and past ice sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore , one should distinguish various types of floating glaciers according to their dynami cs, described by different models . In this paper the symbols are mainly as in the previous paper (Grigoryan and others, 1976) so no list of symbols is provided here.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore , one should distinguish various types of floating glaciers according to their dynami cs, described by different models . In this paper the symbols are mainly as in the previous paper (Grigoryan and others, 1976) so no list of symbols is provided here.• This paper was accep ted fo r the In ternat iona l Symposium on th e Th erm al R egime of Glaciers and I ce Shee ts, Burnaby, Canada, April 1975, but was not presented becau se of the absence of the a uthors . …”
mentioning
confidence: 99%